Queering public health and public policy in the Deep South - Strunk, Kamden K.; Fieszil, Raina Hafftka (Emerald Publishing Limited : Information Age Publishing, 2020)
"In this volume, authors explore the interconnected issues of public health and public policy as they relate to queer issues in the Deep South. The book begins with a sustained examination of public health, health disparities, and mental health for LGBTQ people in the South. Next, the issues of public policy and public advocacy, including law enforcement, community advocacy and activism, and public life in the Deep South are taken up. Through the chapters in this text, the peculiarities of public health and public policy for LGBTQ people in the Deep South are explored. However, this volume also points to trends, themes, and dynamics at work in the Deep South that are also implicated in the queer experience in other parts of the U.S. The authors of this text push readers to think deeply about these issues. They clearly highlight the systemic nature of oppression of queer people in the South through institutions of medicine, mental health discourses, the criminal justice system, and public life including Pride and Mardi Gras. Taken together, the authors in this volume call for reform, liberation, and conscientization and queerly envision the future of health and policy in the Deep South"-- Provided by publisher.
Keywords: Sexual minorities -- Medical care -- Southern States.; Sexual minorities -- Mental health services -- Southern States.; Discrimination in medical care -- Southern States.; Discrimination in mental health services -- Southern States.; Medical -- Health Care Delivery.; Care of people with mental health issues.; Health systems and services.; elektronické knihy; electronic books